The Physics of Complex Systems (New Advances and Perspectives) - Mallamace, F (IOS Press, 2013)
This volume contains all the lectures presented at the CLV Course of the International School of Physics “Enrico Fermi” held on 1–11 July 2003 in Varenna, Italy. They focus on recent advances and perspectives in the physics of complex systems and provide both an overview of the field and a more detailed examination of the new ideas and unsolved problems that are currently attracting the attention of researchers. Although all of the lecturers have made important contributions within their individual areas, and most have made significant contributions to the field as a whole, this collection is pedagogically focused so that the material will be accessible to a wider audience. We hope that this published form of the lectures will augment the pedagogical utility of the presentations. Bear in mind that the field of complex systems is very broad and that no single volume can be truly comprehensive.